ADAPTATION ANALYSIS OF AMERICAN VIDEO GAMES MORTAL KOMBAT INTO FILM MORTAL KOMBAT REBOOT 2021 - Arya Saputra; Rista Nur Kholifah; Salman Alfarisi (CrossOver, 2022)
Nowadays, many games are transformed into adaptation works. One of them is Mortal Kombat Game, adapted into Film Mortal Kombat Reboot 2021. Using these objects, the Mortal Kombat Game and its film adaptations Mortal Kombat Reboot 2021, this research analyzes the movie adaptation process since it contains some changes and omissions. The changes are inevitable because the media is transformed, which was originally in the form of game and adapted into a version with a shorter duration, a movie. This is in accordance with Hutcheon’s adaptation theory in the Interacting to Showing section, which is also used as the main theory to analyze the object of this research. There are also differences in terms of audiovisual and interaction with the audience. There are two problem formulations to be discussed in this research. First, what changes are made in the movie adaptation, and second, the consequences of differences in media of the stories in the games and films. To conduct this research, we use the descriptive comparative method to explain the differences. This method supports written information and pictures, which is important to study this article. The results of the research reveal that there are two changes that occur in this film adaptation. First, there are five different character visualizations and one additional character, and second, four plot changes. The researchers conclude that the adaptation made by the film production team is not much different from the appearance of the characters and the plot of the original game. Thus, the adapter does not completely change it from the original game but only expands it as a new story made for the film, but keeps the game as the main reference.